Budaya Kreatif Mahasiswa di Masa Pandemi Covid-19; Sebuah Fenomena Kehidupan Sosial Mahasiswa FISIP UINSA - Setiyani, Wiwik; Suhartini, Rr (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2021)
The covid-19 pandemic did not cause a negative effect to student life. On the other hand, it brings the creativity to erase the boredom. Studying at home fosters a variety of student creativity to create a good works, in the form of writing or raising the skill in cooking, sewing, gardening, and so on. Those social phenomenon is a form of creative culture that comes in the middle of pandemic era. Student creativity is an interaction between the three forces, first, storing and delivering cultural ideas of faith in the next generation. Second, the social system which contains of behavior, values and information (memes). Third, the individual who brings the transformation unit into the social-cultural domain. This article is focused on the creative culture of scholar in FISIP UINSA to response the pandemic of covid-19. The methodology that used in this article based on the result of scholar ethnography survey through Google form. The interaction of scholar in social media bring the change in behavior to be able communicating with other people. Blog becomes the media to share the creativity by creating the positive content. Creative culture is a reflection of student who can use the time wisely to continue their creativity to be more valuable and meaningful. It because the creativity comes from the interaction between individual, social and cultural system that appear as a community life.